-7y^{2}(-4y^{3}+6y)
15xy^{4}+60x^{2}y^{3}
-7y^{2}(-4y^{3}+6y)
15xy^{4}+60x^{2}y^{3}
-7y2(-4y3+6y) -> factorize the coefficients we get
-7 y2 (- 2.2.y3 + 2.3.y) -> take the 2's in front out of the parenthesis
- 7.2 y2 (-2.y3 + 3.y) -> take one y in front out of the parenthesis
-14 y3 (-2 y2 + 3) -> take a minus sign -1 in front out of the parenthesis
14 y3 (2 y2 - 3)
For the second polynomial
15xy4+60x2y3
15 x y4 + 4.15 x2 y3 -> take 15 in front and set parenthesis
15 (x y4 + 4 x2 y3) -> take one x in front
15 x ( y4 + 4 x y3) -> take y3 in front
15 x y3 ( y + 4 x)
Comments
step-by-step please